CIMPAL-based assessment of cumulative biological pressures from invasive alien species, jellyfish blooms, and harmful algal blooms in the Italian Adriatic Sea - Serena Zampardi; Patrizia Perzia; Tiziana Cillari; Luca Castriota; Emanuela Spada; Patrizia Borrello; Danilo Scannella; Manuela Falautano; Teresa Maggio; Giulio Farella; Giuseppe Scarcella; Laura Sabatini; et al. (Ocean & Coastal Management, 2026)

Assessment of Bottom Trawl Impacts on the Status of Seabed Communities in European Seas - Jan Geert Hiddink; Sebastian Valanko; Luke Batts; Esther D. Beukhof; Mats Blomqvist; Stefan Bolam; Belén Calero; Michele Casini; Marina Delgado; Jochen Depestele; Joanna Desmidt; Gabriele Di Bona; et al. (Fish and Fisheries, 2026)
Bottom trawling affects seabed habitats, but its large‐scale impacts remain poorly quantified. Assessment of trawling impacts is essential to support monitoring and achieving sustainability objectives under international conventions, sustainable development goals, and seafood certification programs. We present a Europe‐wide quantitative assessment of bottom trawling impacts, accounting for regional seabed‐community sensitivity drivers, across the Baltic, Atlantic, Mediterranean and Black Sea continental shelves. Using two risk‐based indicators of seabed status—Relative Benthic Status determined as benthic community biomass relative to seabed fauna carrying capacity (RBS tot ) and RBS sen (biomass of the 10% most sensitive fauna relative to carrying capacity)—we found substantial regional and habitat differences. The Black, Baltic and Aegean‐Levantine Seas showed low trawling intensity and high seabed status across habitats. In contrast, the Western Mediterranean, Ionian and Central Mediterranean and Adriatic Seas were the most severely impacted. Trawling affected the sensitive species biomass fraction more strongly than the total community biomass. RBS tot was in good condition (here chosen as RBS > 75% for epifauna) for over 79% of habitat‐ecoregion combinations. In contrast, RBS sen met this threshold in only 46% of these. A strong correlation emerged between the mean trawling intensity and RBS tot and RBS sen , allowing the use of SAR to estimate ecosystem status. This relationship can support decisions on where, and by how much, SAR reductions are needed to achieve good environmental status in regions where no detailed assessment is available. Our approach provides a quantitative framework to balance fishery production with ecosystem sustainability, offering tools for environmental and fisheries management in Europe.

Enhancing scientific knowledge to support the exploitation of invasive Anadara spp. in the Adriatic Sea - Marina Chiappi; Ernesto Azzurro; Pierluigi Strafella; Carmen Ferrà; Francesca Luzi; Stefano Guicciardi; Giorgio Mancinelli; Alessio Bonaldo; Antonina De Marco; Beatrice Fracasso; Sara Mancarella; Chiara Roberta Girelli; et al. (Marine Policy, 2025)

Applying a regional certification scheme for aquatic invasive species fishery: The case of blue crab (Callinectes sapidus) in the northern Adriatic Sea - Sara Bonanomi; Simone Libralato; Loretta Malvarosa; Karolina Maria Czechowska; Giulia Sandalli; Alessia Cariani; Alice Ferrari; Ernesto Azzurro; Giuseppe Scarcella (Marine Policy, 2025)

Managing the starry ray (Raja asterias) in the mid-western Adriatic Sea: why sex matters in fisheries conservation - Giada Bargione; Andrea Pardini; Fortunata Donato; Daniel Li Veli; Laura Sabatini; Emily Sepe; Giuseppe Scarcella; Alessandro Lucchetti (Frontiers in Marine Science, 2025)
The starry ray, Raja asterias (Delaroche 1809), is a demersal Mediterranean skate often caught as bycatch in bottom trawls and set nets. Due to high fishing pressure in the Adriatic Sea, key life history traits were investigated to support effective conservation and fishery management. Specimens were collected from 2019 to 2023 through both fishery-dependent and independent sampling in the mid-western Adriatic. Age was estimated for the first time in cartilaginous fish using burnt and dissected vertebrae. The reproductive cycle was assessed through macroscopic gonad examination, while spatial distribution was analyzed in relation to sex and maturity (mature vs immature). Trends in relative abundance and biomass (2007–2024) were evaluated using standardized survey data. Results revealed significant sexual dimorphism in biological traits. Females showed a broader size range (170–590 mm vs 160–505 mm), greater disc width (115–410 mm vs 105–342 mm), and positive allometric growth, compared to isometric growth in males. Growth patterns also differed: Von Bertalanffy parameters were L ∞ = 724, k = 0.28 for females and L ∞ = 574, k = 0.44 for males. Females reached greater maximum age (4.5 vs 4.0 years), and achieved sexual maturity at larger sizes (425 vs 360 mm) and older ages (approx. 3.0 vs 2.0 years). Spatial analysis showed that immature individuals are concentrated nearshore (<50 m depth), while mature ones inhabit deeper waters (up to 80 m). During the reproductive season, adults migrate inshore, overlapping with immature habitats. Abundance and biomass indices significantly increased over time, particularly after 2020. These findings underscore the need for sex-specific biological parameters in management strategies. Conservation measures should avoid using population-wide averages and instead adopt the most precautionary approach. Additionally, limiting fishing in shallow waters could reduce bycatch of immature or egg-laying individuals for much of the year, positively impacting population recovery.

Gap Analysis on the Biology of Marine Fishes Across European Seas - Kathleen Kesner-Reyes; Emily C. Capuli; Rodolfo B. Reyes; Jeremiah Glenn M. Jansalin; Josephine Rius-Barile; Manuel Bactong; Eva Daskalaki; Sophie Manousi; Carmen Ferrà; Giuseppe Scarcella; Gianpaolo Coro; Francesc Ordines; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Comparison of the reproductive cycles of two cryptic soles in the Adriatic Sea - Laura Sabatini; Fortunata Donato; Mario La Mesa; Emanuela Fanelli; Giuseppe Scarcella (Animal Reproduction Science, 2025)

The stock status of narrow-barred Spanish mackerel, Scomberomorus commerson (Lacépède, 1800) in the southern Arabian Gulf: a case study using multiple length-based assessment approaches - Mohamed AlMusallami; Mark Dimech; Franklin Francis; Waleed Hamza; Aaron C. Henderson; Sabir Bin Muzaffar; Giuseppe Scarcella; Nazli Demirel; Dario Pinello (Frontiers in Marine Science, 2025)
This study evaluates the stock status of Scomberomorus commerson in the southern Arabian Gulf, particularly in Abu Dhabi waters, using length-based models to address data limitations in fisheries assessments. The findings contribute critical insights into management practices using four length-based models, namely, LBI, LBB, LBSPR, and LIME, to analyze length frequency distributions from commercial catches between 2011 and 2023. The results indicate that the stock is overfished, with low proportions of mature and optimal-sized individuals and an excessive harvest of juveniles, as shown by the model estimates of F/M ratios and SPR values below target levels. From 2011 to 2019, the biomass declined sharply, but signs of recovery were evident by 2023 due to management actions, such as a gillnet ban introduced in 2019. The final-year estimates revealed a B/Bmsy ratio of 1.0 and F/M of 1.2, suggesting ongoing but reduced overfishing pressures. These outcomes underscore the importance of ongoing data-limited assessment methods in monitoring exploited stocks, providing evidence that restrictive measures have positively impacted biomass recovery. The convergence of outputs across methods, such as the indication of overfishing in S. commerson stocks, suggests that implementing multiple models enhances the robustness of management recommendations, including the enforcement of minimum size limits or reductions in fishing efforts or restriction of certain fishing methods. Overall, this study highlights the importance of using multiple models and choosing appropriate priors to improve the quality of stock assessments in data-limited fisheries.

Spatial distribution and life history traits of two sympatric, cryptic species of sole in the Adriatic Sea basin - LAURA SABATINI; FORTUNATA DONATO; MARIO LA MESA; GIUSEPPE SCARCELLA; EMANUELA FANELLI (Mediterranean Marine Science, 2025)
The common sole, Solea solea (Linnaeus, 1758), one of the main fishery demersal resources in the Mediterranean, coexists in the Adriatic Sea with the Egyptian sole, Solea aegyptiaca (Chabanaud, 1927), which is a congeneric and cryptic species. This study, for the first time in this basin, investigated the spatial distribution of the Egyptian sole by combining all data available from fishery dependent and independent sampling activities and comparing certain life history traits of the two sole species. The Egyptian sole was common in the north-western coastal waters, with a concentration area of juveniles around the Po River mouth and larger individuals on medium sandy sediments associated with ancient delta systems in the central part of the Gulf of Venice. The hypothesis posits that these areas serve as essential habitats for the Egyptian sole. The two sole species exhibited similar characteristics, with positive allometric growth and sexual dimorphism. An analogous growth trend was observed during ontogeny, characterized by fast growth until the second year of life, with maximum size achievement starting from the third year of life. Both species have the potential to attain lifespans exceeding 10 years. All these analogies confirmed their classification as cryptic species. The hypothesis posits that the two species rely on olfactory sense rather than visual signals for intraspecific recognition. This study represents an initial endeavor to elucidate the characterizing traits and habits that enable these two sibling soles to coexist as distinct species, thereby providing useful information to support resource assessment and management in the Adriatic Sea.

A multidisciplinary approach to describe population structure of Solea solea in the Mediterranean Sea - Rachele Corti; Elisabetta Piazza; Enrico Nicola Armelloni; Alice Ferrari; Audrey J. Geffen; Gregory E. Maes; Francesco Masnadi; Castrense Savojardo; Giuseppe Scarcella; Marco Stagioni; Fausto Tinti; Alex Zemella; et al. (Frontiers in Marine Science, 2024)
Investigating marine species population structure in a multidisciplinary framework can reveal signatures of potential local adaptation and the consequences for management and conservation. In this study we delineate the population structure of common sole ( Solea solea ) in the Mediterranean Sea using genomic and otolith data, based on single nucleotide polymorphism (SNPs) markers, otolith shape and otolith trace element composition data. We correlated SNPs with environmental and spatial variables to evaluate the impact of the selected features on the actual population structure. Specifically, we used a seascape genetics approach with redundancy (RDA) and genetic-environmental association (GEA) analysis to identify loci potentially involved in local adaptation. Finally, putative functional annotation was investigated to detect genes associated with the detected patterns of neutral and adaptive genetic variation. Results from both genetic and otolith data suggested significant divergence among putative populations of common sole, confirming a clear separation between the Western and Eastern Mediterranean Sea, as well as a distinct genetic cluster corresponding to the Adriatic Sea. Evidence of fine-scale population structure in the Western Mediterranean Sea was observed at outlier loci level and further differentiation in the Adriatic. Longitude and salinity variation accounted for most of the wide and fine spatial structure. The GEA detected significant associated outlier loci potentially involved in local adaptation processes under highly structured differentiation. In the RDA both spatial distribution and environmental features could partially explain the genetic structure. Our study not only indicates that separation among Mediterranean sole population is led primarily by neutral processes because of low connectivity due to spatial segregation and limited dispersal, but it also suggests the presence of local adaptation. These results should be taken into account to support and optimize the assessment of stock units, including a review and possible redefinition of fishery management units.

Identifying priority areas for spatial management of mixed fisheries using ensemble of multi‐species distribution models - Diego Panzeri; Tommaso Russo; Enrico Arneri; Roberto Carlucci; Gianpiero Cossarini; Igor Isajlović; Svjetlana Krstulović Šifner; Chiara Manfredi; Francesco Masnadi; Marco Reale; Giuseppe Scarcella; Cosimo Solidoro; et al. (Fish and Fisheries, 2024)
Spatial fisheries management is widely used to reduce overfishing, rebuild stocks, and protect biodiversity. However, the effectiveness and optimization of spatial measures depend on accurately identifying ecologically meaningful areas, which can be difficult in mixed fisheries. To apply a method generally to a range of target species, we developed an ensemble of species distribution models (e‐SDM) that combines general additive models, generalized linear mixed models, random forest, and gradient‐boosting machine methods in a training and testing protocol. The e‐SDM was used to integrate density indices from two scientific bottom trawl surveys with the geopositional data, relevant oceanographic variables from the three‐dimensional physical‐biogeochemical operational model, and fishing effort from the vessel monitoring system. The determined best distributions for juveniles and adults are used to determine hot spots of aggregation based on single or multiple target species. We applied e‐SDM to juvenile and adult stages of 10 marine demersal species representing 60% of the total demersal landings in the central areas of the Mediterranean Sea. Using the e‐SDM results, hot spots of aggregation and grounds potentially more selective were identified for each species and for the target species group of otter trawl and beam trawl fisheries. The results confirm the ecological appropriateness of existing fishery restriction areas and support the identification of locations for new spatial management measures.

Scientific knowledge gaps on the biology of non-fish marine species across European Seas - Luisa R. Abucay; Patricia Sorongon-Yap; Kathleen Kesner-Reyes; Emily C. Capuli; Rodolfo B. Reyes; Eva Daskalaki; Carmen Ferrà; Giuseppe Scarcella; Gianpaolo Coro; Francesc Ordines; Paula Sánchez-Zulueta; Georgi Dakalov; et al. (Frontiers in Marine Science, 2023)
Available information and potential data gaps for non-fish marine organisms (cnidarians, crustaceans, echinoderms, molluscs, sponges, mammals, reptiles, and seabirds) covered by the global database SeaLifeBase were reviewed for eight marine ecosystems (Adriatic Sea, Aegean Sea, Baltic Sea, Bay of Biscay/Celtic Sea/Iberian Coast , Black Sea, North Sea, western Mediterranean Sea, Levantine Sea) across European Seas. The review of the SeaLifeBase dataset, which is based on published literature, analyzed information coverage for eight biological characteristics (diet, fecundity, maturity, length-weight relationships, spawning, growth, lifespan, and natural mortality). These characteristics are required for the development of ecosystem and ecological models to evaluate the status of marine resources and related fisheries. Our analyses revealed that information regarding these biological characteristics in the literature was far from complete across all studied areas. The level of available information was nonetheless reasonably good for sea turtles and moderate for marine mammals in some areas (Baltic Sea, Bay of Biscay/Celtic Sea/Iberian Coast , Black Sea, North Sea and western Mediterranean Sea). Further, seven of the areas have well-studied species in terms of information coverage for biological characteristics of some commercial species whereas threatened species are generally not well studied. Across areas, the most well-studied species are the cephalopod common cuttlefish ( Sepia officinalis) and the crustacean Norway lobster ( Nephrops norvegicus ). Overall, the information gap is narrowest for length-weight relationships followed by growth and maturity, and widest for fecundity and natural mortality. Based on these insights, we provide recommendations to prioritize species with insufficient or missing biological data that are common across the studied marine ecosystems and to address data deficiencies.

Otolith shape analysis as a tool for stock identification of two commercially important marine fishes: Helicolenus dactylopterus and Merluccius merluccius - Ana Vaz; Milene Alexandra Guerreiro; Jorge Landa; Olsen Hannipoula; Ioannis Thasitis; Giuseppe Scarcella; Laura Sabatini; Sergio Vitale; Estanis Mugerza; Kélig Mahé; Patrick Reis-Santos; Susanne E. Tanner; et al. (Estuarine, Coastal and Shelf Science, 2023)

Assessment of the current status and effectiveness of area-based conservation measures banning trawling activities in the Adriatic Sea - Carmen Ferrà; Giuseppe Scarcella (Frontiers in Marine Science, 2023)
The marine environment is highly stressed by anthropogenic pressures, among which fisheries, and in particular bottom trawling, are one of the main sources of impact. Area-based conservation measures can help conserve and restore ecosystems and population structures and therefore constitute a key tool to the achievement of the 14th Sustainable Development Goal, preservation of the ocean. The purpose of this paper is to provide an assessment of the compliance of area-based conservation measures. The Adriatic Sea has been selected as a case study area, as one of the most intensively trawled areas in the world where different countries share its resources and consequently different management strategies are put in place. We present a review of the marine managed areas established in the Adriatic Sea in 2019, providing information on their characteristics, temporal variabilities, and scopes. Through the processing of Automatic Identification System (AIS) data, the monthly bottom fishing activity performed within each area was inferred and the intensity was assessed. Thus, the effectiveness of trawling bans was evaluated. We demonstrated that full respect of the prohibition was effective in 73% of the areas, while trawling activity was recorded with different intensities in 149 out of 549 managed areas.

Biphasic versus monophasic growth curve equation, an application to common sole (Solea solea, L.) in the northern and central Adriatic Sea - Pierluigi Carbonara; Francesco Masnadi; Fortunata Donato; Laura Sabatini; Giulio Pellini; Massimiliano Cardinale; Giuseppe Scarcella (Fisheries Research, 2023)

Editorial: Data-limited research in stock assessment to increase the understanding of fisheries resources and inform and improve management efforts - Giuseppe Scarcella; Simone Libralato; Natalie Anne Dowling; Joanna Mills Flemming; Matthias Wolff (Frontiers in Marine Science, 2023)

Data availability and participatory approach: the right mix for enhancing Mediterranean fisheries’ sustainability - Loretta Malvarosa; Gualtiero Basilone; Pierluigi Carbonara; Paolo Carpentieri; Maria Cozzolino; Maria Cristina Follesa; Monica Gambino; Vita Gancitano; David Parreno Duque; Paola Pesci; Ilaria Vielmini; Giuseppe Scarcella (Frontiers in Marine Science, 2023)
A misalignment between the legislation and the effectiveness of Mediterranean fisheries management has emerged due to the status of the stocks (still largely in overfishing) and the discontent of stakeholders regarding management plans and tools that are not always recognized as appropriate to the characteristics of the concerned fisheries. Stakeholders’ involvement in management processes is one of the main pillars of the Common Fisheries Policy revision. The literature underlines, in an increasingly urgent manner, the importance of stakeholders fully understanding the contents of management plans and, vice versa, necessary for the successful implementation of policies. Focusing on the path towards sustainability endorsed by the BluFish project, the paper tries to provide an answer about the sustainability of some selected Southern Italian fisheries, by adopting the assessment approach of the Marine Stewardship Council. The assessment approach, based on a set of Performance Indicators and on a well-defined scoring scheme, focuses on three dimensions of sustainability. In addition to the classic assessment of the state of the stocks, there is an extensive screening of the impact of anthropic activity such as fishing on the entire ecosystem, including both the impact on accessory species and on vulnerable habitats and species. The evaluation adopted goes even further, with an approach that also includes the management and governance sphere, also trying to evaluate the level of involvement of the operators in the decision-making process. The paper illustrates that the selected fisheries are not fully sustainable but some of them have excellent potential for improvement even in the short term by identifying and implementing the appropriate action. The most relevant weaknesses identified refer to the low scores obtained for sustainability of stocks, mainly around the Harvest Control Rules (HCR) and the Harvest Strategy indicators, highlighting the importance of improving the management of the assessed stocks. The paper highlights how data and scientific knowledge availability is essential for a detailed mapping and evaluation of fishing activities but also that the path towards more sustainable and responsible fisheries does not work without a strong participation of all the key stakeholders.

Is the Small-Scale Fishery more sustainable in terms of GHG emissions? A case study analysis from the Central Mediterranean Sea - Francesco Cavraro; Marco Anelli Monti; Alberto Caccin; Fabio Fiori; Fabio Grati; Elisabetta Russo; Giuseppe Scarcella; Dario Vrdoljak; Sanja Matić-Skoko; Fabio Pranovi (Marine Policy, 2023)

The potential effects of COVID-19 lockdown and the following restrictions on the status of eight target stocks in the Adriatic Sea - Giuseppe Scarcella; Silvia Angelini; Enrico Nicola Armelloni; Ilaria Costantini; Andrea De Felice; Stefano Guicciardi; Iole Leonori; Francesco Masnadi; Martina Scanu; Gianpaolo Coro (Frontiers in Marine Science, 2022)
The COVID-19 pandemic had major impacts on the seafood supply chain, also reducing fishing activity. It is worth asking if the fish stocks in the Mediterranean Sea, which in most cases have been in overfishing conditions for many years, may have benefitted from the reduction in the fishing pressure. The present work is the first attempt to make a quantitative evaluation of the fishing effort reduction due to the COVID-19 pandemic and, consequently, its impact on Mediterranean fish stocks, focusing on Adriatic Sea subareas. Eight commercially exploited target stocks (common sole, common cuttlefish, spottail mantis shrimp, European hake, red mullet, anchovy, sardine, and deepwater pink shrimp) were evaluated with a surplus production model, separately fitting the data for each stock until 2019 and until 2020. Results for the 2019 and 2020 models in terms of biomass and fishing mortality were statistically compared with a bootstrap resampling technique to assess their statistical difference. Most of the stocks showed a small but significant improvement in terms of both biomass at sea and reduction in fishing mortality, except cuttlefish and pink shrimp, which showed a reduction in biomass at sea and an increase in fishing mortality (only for common cuttlefish). After reviewing the potential co-occurrence of environmental and management-related factors, we concluded that only in the case of the common sole can an effective biomass improvement related to the pandemic restrictions be detected, because it is the target of the only fishing fleet whose activity remained far lower than expectations for the entire 2020.

Filling Gaps in Trawl Surveys at Sea through Spatiotemporal and Environmental Modelling - Gianpaolo Coro; Pasquale Bove; Enrico Nicola Armelloni; Francesco Masnadi; Martina Scanu; Giuseppe Scarcella (Frontiers in Marine Science, 2022)
International scientific fishery survey programmes systematically collect samples of target stocks’ biomass and abundance and use them as the basis to estimate stock status in the framework of stock assessment models. The research surveys can also inform decision makers about Essential Fish Habitat conservation and help define harvest control rules based on direct observation of biomass at the sea. However, missed survey locations over the survey years are common in long-term programme data. Currently, modelling approaches to filling gaps in spatiotemporal survey data range from quickly applicable solutions to complex modelling. Most models require setting prior statistical assumptions on spatial distributions, assuming short-term temporal dependency between the data, and scarcely considering the environmental aspects that might have influenced stock presence in the missed locations. This paper proposes a statistical and machine learning based model to fill spatiotemporal gaps in survey data and produce robust estimates for stock assessment experts, decision makers, and regional fisheries management organizations. We apply our model to the SoleMon survey data in North-Central Adriatic Sea (Mediterranean Sea) for 4 stocks: Sepia officinalis , Solea solea , Squilla mantis , and Pecten jacobaeus . We reconstruct the biomass-index (i.e., biomass over the swept area) of 10 locations missed in 2020 (out of the 67 planned) because of several factors, including COVID-19 pandemic related restrictions. We evaluate model performance on 2019 data with respect to an alternative index that assumes biomass proportion consistency over time. Our model’s novelty is that it combines three complementary components. A spatial component estimates stock biomass-index in the missed locations in one year, given the surveyed location’s biomass-index distribution in the same year. A temporal component forecasts, for each missed survey location, biomass-index given the data history of that haul. An environmental component estimates a biomass-index weighting factor based on the environmental suitability of the haul area to species presence. Combining these components allows understanding the interplay between environmental-change drivers, stock presence, and fisheries. Our model formulation is general enough to be applied to other survey data with lower spatial homogeneity and more temporal gaps than the SoleMon dataset.

ClimateFish: A Collaborative Database to Track the Abundance of Selected Coastal Fish Species as Candidate Indicators of Climate Change in the Mediterranean Sea - Ernesto Azzurro; Tosca Ballerini; Chryssanthi Antoniadou; Giulia Domizia Aversa; Jamila Ben Souissi; Andrea Blašković; Valentina Cappanera; Marina Chiappi; Maria-Francesca Cinti; Francesco Colloca; Ivan Cvitković; Manuela D’Amen; et al. (Frontiers in Marine Science, 2022)

Understanding the Dynamics of Ancillary Pelagic Species in the Adriatic Sea - Silvia Angelini; Enrico N. Armelloni; Ilaria Costantini; Andrea De Felice; Igor Isajlović; Iole Leonori; Chiara Manfredi; Francesco Masnadi; Giuseppe Scarcella; Vjekoslav Tičina; Alberto Santojanni (Frontiers in Marine Science, 2021)
The status of fishery resources in the Mediterranean Sea is critical: most of the fish and shellfish stocks are in overexploitation and only half of them are routinely assessed. This manuscript presents the use of Surplus Production Models (SPMs) as a valid option to increase the number of assessed stocks, with specific attention to the Adriatic basin. Particularly, the stock of European sprat ( Sprattus sprattus ), Mediterranean horse mackerel ( Trachurus mediterraneus ), and Atlantic horse mackerel ( Trachurus trachurus ) living in the Adriatic Sea have been evaluated comparing three SPMs: Catch Maximum Sustainable Yields (CMSY), Stochastic surplus Production model in Continuous Time (SPiCT), and Abundance Maximum Sustainable Yields (AMSY). The different approaches present some variations; however, they generally agree on describing all the stocks close to the reference values for both biomass and fishing mortality in the most recent year. For the European sprat, AMSY results are the most robust model for this species’ survey data allow depicting a clearer picture of the history of this stock. Indeed, for the horse mackerel species, CMSY or SPiCT results are the preferred models, since for these species landings are not negligible. Notwithstanding, age-structured assessments remain the most powerful approach for evaluating the status of resources, but SPMs have proved to be a powerful tool in a data-limited context.

Nephrops norvegicus in the Adriatic Sea: Connectivity modeling, essential fish habitats, and management area network - Donata Melaku Canu; Célia Laurent; Elisabetta B. Morello; Stefano Querin; Giuseppe Scarcella; Nedo Vrgoc; Carlo Froglia; Silvia Angelini; Cosimo Solidoro (Fisheries Oceanography, 2021)
Knowledge of connectivity among subpopulations is fundamental in the identification of the appropriate geographical scales for stock status evaluation and management, the identification of areas with greater retention rates, and space‐based fisheries management. Here, an integration of hydrodynamic, biological, and habitat models results is used to assess connectivity and support the definition of essential fish habitats (EFH) in the Adriatic Sea, with reference to Nephrops norvegicus , an important benthic commercial resource, the recruitment of which is strongly related to larval dispersal from spawning to recruitment areas. We explored oceanographic and biological connectivity in the Adriatic Sea under a wide and representative variety of oceanographic conditions (winters 2006–2012) by tracking 3D trajectories of larvae released from different areas. We used a Lagrangian model that features a specific larval behavior module with explicit dependence on environmental parameters (i.e., temperature and sediment type) and that is driven by high‐resolution hydrodynamic and meteorological data. The results were used to partition the area in which Nephrops was observed into 20 homogenous management subareas; to assess the connection between spawning, recruitment, and harvesting grounds; and to identify potential subpopulation boundaries as well as the connectivity among the potential subpopulations. The results suggest the presence of at least three distinct subpopulations, which need to be independently managed and conserved, and confirms that the Jabuka‐Pomo pit is the most important spawning area, but alone it cannot sustain Nephrops populations throughout the Adriatic Sea. The results also show the importance to move from particle‐tracking to approaches based on integrated models.

Data Poor Approach for the Assessment of the Main Target Species of Rapido Trawl Fishery in Adriatic Sea - Enrico Nicola Armelloni; Martina Scanu; Francesco Masnadi; Gianpaolo Coro; Silvia Angelini; Giuseppe Scarcella (Frontiers in Marine Science, 2021)
Information on stock status is available only for a few of the species forming the catch assemblage of rapido fishery of the North-central Adriatic Sea (Mediterranean Sea). Species that are caught almost exclusively by this gear, either as target (such as Pectinidae ) or accessory catches (such as flatfishes apart from the common sole), remain unassessed mainly due to the lack of data and biological information. Based on cluster analysis, the catch assemblage of this fishery was identified and assessed using CMSY model. The results of this data-poor methodology showed that, among the species analyzed, no one is sustainably exploited. The single-species CMSY results were used as input to an extension of the same model, to test the effect of four different harvest control rule (HCR) scenarios on the entire catch assemblage, through 15-years forecasts. The analysis showed that the percentage of the stocks that will reach B msy at the end of the projections will depend on the HCR applied. Forecasts showed that a reduction of 20% of fishing effort may permit to most of the target and accessory species of the rapido trawl fishery in the Adriatic Sea to recover to B msy levels within 15 years, also providing a slight increase in the expected catches.

Using AIS to Attempt a Quantitative Evaluation of Unobserved Trawling Activity in the Mediterranean Sea - Carmen Ferrà; Anna Nora Tassetti; Enrico Nicola Armelloni; Alessandro Galdelli; Giuseppe Scarcella; Gianna Fabi (Frontiers in Marine Science, 2020)
In the past decades, the Automatic Identification System (AIS) has been employed in numerous research fields as a valuable tool for, among other things, Maritime Domain Awareness and Maritime Spatial Planning. In contrast, its use in fisheries management is hampered by coverage and transmission gaps. Transmission gaps may be due to technical limitations (e.g., weak signal or interference with other signals) or to deliberate switching off of the system, to conceal fishing activities. In either case such gaps may result in underestimating fishing effort and pressure. This study was undertaken to map and analyze bottom trawler transmission gaps in terms of duration and distance from the harbor with a view to quantifying unobserved fishing and its effects on overall trawling pressure. Here we present the first map of bottom trawler AIS transmission gaps in the Mediterranean Sea and a revised estimate of fishing effort if some gaps are considered as actual fishing.

Response: Commentary: The Saga of the Management of Fisheries in the Adriatic Sea: History, Flaws, Difficulties, and Successes Toward the Application of the Common Fisheries Policy in the Mediterranean - Massimiliano Cardinale; Piera Carpi; Giuseppe Scarcella (Frontiers in Marine Science, 2019)

Water temperature gradients drive early life-history patterns of the common sole (Solea solea L.) in the Northeast Atlantic and Mediterranean - Ana Catarina Vaz; Giuseppe Scarcella; Miguel A. Pardal; Filipe Martinho (Aquatic Ecology, 2019)

The Saga of the Management of Fisheries in the Adriatic Sea: History, Flaws, Difficulties, and Successes toward the Application of the Common Fisheries Policy in the Mediterranean - Piera Carpi; Giuseppe Scarcella; Massimiliano Cardinale (Frontiers in Marine Science, 2017)

Anadara kagoshimensis (Mollusca: Bivalvia: Arcidae) in Adriatic Sea: morphological analysis, molecular taxonomy, spatial distribution, and prediction - PIERLUIGI STRAFELLA; ALICE FERRARI; GIANNA FABI; VERA SALVALAGGIO; ELISA PUNZO; CLARA CUICCHI; ANGELA SANTELLI; ALESSIA CARIANI; FAUSTO TINTI; ANNA NORA TASSETTI; GIUSEPPE SCARCELLA (Mediterranean Marine Science, 2017)
Morphological analysis, molecular characterization, and information on distribution and density of Anadara kagoshimensis (Tokunaga, 1906) specimens collected in the Adriatic Sea were here carried out as based on various material and data from five surveys conducted from 2010 to 2014, for a total of 329 bottom trawl hauls. The morphological and molecular analyses allowed to clarify the confused taxonomy regarding the biggest ark clam alien species invading the Italian waters and the Mediterranean Sea. The analysis on distribution and density revealed that A. kagoshimensis mostly occurs along the Italian coast at depths from 8 to 50 m, with a catch frequency of more than 98% in all hauls performed on silty-clay sediment at 8-30 m depth. The hotspot map clearly shows a reduction of its distribution area from 2010 to 2012.

Recent Trends and Impacts of Fisheries Exploitation on Mediterranean Stocks and Ecosystems - Francesco Colloca; Giuseppe Scarcella; Simone Libralato (Frontiers in Marine Science, 2017)

Comparison of Lindane and Carbaryl Pesticide Bioaccumulation in the Common Sole (Solea solea) - Frapiccini Emanuela; Scarcella Giuseppe; Guicciardi Stefano; Betti Mattia; Marini Mauro (Bulletin of Environmental Contamination and Toxicology, 2017)

Mediterranean Sea: A Failure of the European Fisheries Management System - Massimiliano Cardinale; Giacomo Chato Osio; Giuseppe Scarcella (Frontiers in Marine Science, 2017)

CMV infection in a cohort of HIV-exposed infants born to mothers receiving antiretroviral therapy during pregnancy and breastfeeding - Maria Franca Pirillo; Giuseppe Liotta; Mauro Andreotti; Haswel Jere; Jean-Baptiste Sagno; Paola Scarcella; Sandro Mancinelli; Ersilia Buonomo; Roberta Amici; Maria Cristina Marazzi; Stefano Vella; Leonardo Palombi; et al. (Medical Microbiology and Immunology, 2017)

Nursery habitat colonization by juvenile sole (Solea solea L.) in the North Atlantic and Mediterranean – a latitudinal perspective - Vaz Ana; Scarcella Giuseppe; Pardal Miguel; Martinho Filipe (Frontiers in Marine Science, 2015)

Rebuilding Mediterranean fisheries: a new paradigm for ecological sustainability - Francesco Colloca; Massimiliano Cardinale; Francesc Maynou; Marianna Giannoulaki; Giuseppe Scarcella; Klavdija Jenko; Josè Maria Bellido; Fabio Fiorentino (Fish and Fisheries, 2013)
In Mediterranean European countries, 85% of the assessed stocks are currently overfished compared to a maximum sustainable yield reference value (MSY) while populations of many commercial species are characterized by truncated size‐ and age‐structures. Rebuilding the size‐ and age‐structure of exploited populations is a management objective that combines single species targets such as MSY with specific goals of the ecosystem approach to fisheries management (EAF), preserving community size‐structure and the ecological role of different species. Here, we show that under the current fishing regime, stock productivity and fleet profitability are generally impaired by a combination of high fishing mortality and inadequate selectivity patterns. For most of the stocks analysed, a simple reduction in the current fishing mortality ( F cur ) towards an MSY reference value ( F MSY ), without any change in the fishing selectivity, will allow neither stock biomass nor fisheries yield and revenue to be maximized. On the contrary, management targets can be achieved only through a radical change in fisheries selectivity. Shifting the size of first capture towards the size at which fish cohorts achieve their maximum biomass, the so‐called optimal length, would produce on average between two and three times higher economic yields and much higher biomass at sea for the exploited stocks. Moreover, it would contribute to restore marine ecosystem structure and resilience to enhance ecosystem services such as reservoirs of biodiversity and functioning food webs.

Age and growth of the small red scorpionfish, Scorpaena notata Rafinesque, 1810, based on whole and sectioned otolith readings - Giuseppe Scarcella; Mario La Mesa; Fabio Grati; Piero Polidori (Environmental Biology of Fishes, 2011)